Evaluation of economic losses and collapse safety of steel moment frame buildings designed for risk categories II and IV. (15th December 2019) - Hwang, Seong-Hoon; Jeon, Jong-Su; Lee, Kyungkoo
Highlights: Quantify the collapse risk of steel-frame buildings assigned to different risk categories. Assess the earthquake-induced losses for modern code-compliant steel-frame buildings. Utilize metrics to infer the seismic risk of a building for risk-informed decision-making. Discuss the effects of seismic design variable on buildings Abstract: This paper quantifies the collapse risk and earthquake-induced economic loss in low- to mid-rise steel frame buildings assigned to different risk categories, which are designed with perimeter special moment-resisting frames in highly seismic regions in North America. Each archetype building is designed in accordance with two seismic design force levels as permitted within current seismic building code provisions. For this purpose, a probabilistic framework that can explicitly account for various uncertainties inherent in seismic hazard, structural response, and resulting damage is used. It is shown that, depending on the seismic design practice, the collapse risk of the archetype buildings may be of fundamental concern. In this case, it is suggested that the upper-bound design practice, which provides the maximum strength and stiffness to the relevant building, should be used in the structural design process. For moderate-to-high seismic events, the expected economic loss due to building demolition and replacement is the greatest contributor to the total economic losses in low- to mid-rise standard office buildings of an ordinary use, whereas the repair of nonstructural components is the most significant contributor to the total loss in higher-occupancy archetype buildings. For frequent seismic events, the repair to acceleration-controlled nonstructural components accounts for most of the economic losses regardless of assigned risk category.